p-STATISTICAL CONVERGENCE OF ORDER Œ IN PROBABILITY - Akbas, Kubra Elif; Isik, Mahmut (Yokohama Publications, 2024)
In this study, we introduce and examine the concepts of p-statistical convergence of order lX in probability and strong p-summability of order lX in probability. We give sorne relations related with to these concepts. © 2024 Yokohama Publications. All rights reserved.
Keywords: Cesaro summability; random variables; Statistical convergence; statistical convergence in probability